(untitled) (Journal of Informatics Education and Research, 2024)
Background of the study: The rationale of this quantitative research was to corroborate that talent management bolster employee engagement assisting the organization in employee retention. The concept of employee engagement embraces all the dimensions of human resources development. But, when it comes to talent management, engagement strategies alone do not work. To engage a talented employee and to retain is the core thrust of the organization and to find that tactics is the aim of this research. Methodology: A quantitative descriptive, non probability sampling research design was applied for this study. To attain the objective of the research questionnaire was prepared based on various dimensions like professional relationship, job satisfaction, reward management and the like. After validating the questionnaire for its reliability, 122 respondents were selected from various corporate sectors in Chennai City Corporation. Convenience sampling method was employed to collect data for the purpose of analysis. Data measurement uses a Likert scale. SPSS (Statistical Package for Social Science) version 20.0 and MS Excel were used to interpret data. Descriptive statistics like path coefficient original test, cross tabs, factor analysis, chi-square test, total variance, rotated component matrix, cross tabulation were used for analysis. Two step cluster model and nearest neighbor analysis were draw on to represent the reliance of variable. Result/Findings: The study demarcated a dominant association between talent management and the employee engagement and employee retention. The results show that talent management has a contribution towards employee engagement and employee retention. The effect of employee engagement on employee retention could be apprehended if talent management strategies are tuned up according to the need of the hour. Conclusion: Talent management by itself is an approach to attract and motivate proficient and expert employees. By identifying the skill gap and curbing it through skill transformation by applying training, learning and development will not only augment a strong talented workforce but also help in retaining them in the organization.